Colonization and population dynamic of waterbirds in Upper Bisa, Putrajaya Wetlands, Malaysia - Abdul Rahman, Mohd Faid (2012)
Wetlands and its various components play important roles in most waterbirds’ life stages particularly during nesting or breeding stage. The fact that waterbirds are wetland dependent species makes them a valuable indicator to the wetland ecosystem. With the continuous losses and deteriorating quality of the natural wetlands, the use of artificial habitat as a replacement to its natural counterpart is debated by many. Yet the construction of artificial wetlands has been widely carried out as a mean to rehabilitate urban water quality, landscape and also to provide new habitat for the waterbirds to utilize. Recent creation of artificial wetlands in Putrajaya has attracted several waterbirds species to colonize and nest in the area. So far, there is no research conducted on the colonization of waterbirds in artificial wetlands habitat. This opportunity was taken by the researcher to chiefly study the colonization strategies of these waterbirds. The colony is situated in Upper Bisa part of Putrajaya Wetlands (2o56´04.01´´N and 101o42´´12.33´E). This mixed-species colony consists of six waterbirds species which includes Purple heron (Ardea purpurea), Grey heron (Ardea cinerea), Painted stork (Mycteria leucocephala), Night heron (Nycticorax nycticorax), Cattle egret (Bubulcus ibis) and Little egret (Egretta garzetta). They use the wetlands and its surrounding areas for roosting, foraging and nesting. The colony was studied for 18 months from July 2008 to December 2009. Focal observations aided by various equipments like binoculars, spotting scope and cameras with multiple lenses were the primary method used to gather data in this study. As for the result, the nesting waterbirds exhibited varied strategies that were related to their nesting habitat preferences. These include the strategies used during the penetration and establishment period, stratified nesting,nest space partitioning and sharing pattern which are shared by all species. In this study, Purple heron were the dominant competitors and occupied most of the nesting space in the colony area. The con-specific copying mechanism theory and the recruitment theory further explain that Purple heron had the advantages due to its early establishment period. The two critical factors that allow Purple heron to dominate the colony area are arrival time and its occupancy on many of the main foraging sites. These two factors had contributed to the large increase of nesting Purple heron in the colony and consequently attracted other waterbirds to nest in the area. In general, the increase in waterbirds number reflect the potential that these artificial wetlands possess and thus there is a need to monitor and conduct more studies on the colony to address forthcoming issues between the habitat, waterbirds and the public. Integrated management involving responsible authorities as well as support from the scientist particularly in the field of biology and its derivation is the key to initiate this.